Raman analysis of a shocked planetary surface analogue: Implications for habitability on Mars. (14th November 2021) - McHugh, Melissa; Parnell, John; Hutchinson, Ian B.; Lerman, Hannah N.; Edwards, Howell G.M.; Burchell, Mark J.; Cole, Mike J.; Moral, Andoni; Lopez‐Reyes, Guillermo; Perez, Carlos; Arranz, Aurelio; Veneranda, Marco; et al.
Abstract: The scientific aims of the ExoMars Raman laser spectrometer (RLS) include identifying biological signatures and evidence of mineralogical processes associated with life. The RLS instrument was optimised to identify carbonaceous material, including reduced carbon. Previous studies suggest that reduced carbon on the Martian surface (perhaps originating from past meteoric bombardment) could provide a feedstock for microbial life. Therefore, its origin, form, and thermal history could greatly inform our understanding of Mars' past habitability. Here, we report on the Raman analysis of a Nakhla meteorite analogue (containing carbonaceous material) that was subjected to shock through projectile impact to simulate the effect of meteorite impact. The characterisation was performed using the RLS Simulator, in an equivalent manner to that planned for ExoMars operations. The spectra obtained verify that the flight‐representative system can detect reduced carbon in the basaltic sample, discerning between materials that have experienced different levels of thermal processing due to impact shock levels. Furthermore, carbon signatures acquired from the cratered material show an increase in molecular disorder (and we note that this effect will be more evident at higher levels of thermal maturity). This is likely to result from intense shearing forces, suggesting that shock forces within basaltic material may produce more reactive carbon. This result has implications for potential (past) Martian habitability because impacted, reduced carbon may become more biologically accessible. The data presented suggest the RLS instrument will be able to characterise the contribution of impact shock within the landing site region, enhancing our ability to assess habitability. Abstract : Here, we report on the Raman analysis of a Nakhla meteorite analogue (containing carbonaceous material) that was subjected to shock through projectile impact to simulate the effect of meteorite impacts. Characterisation was performed using the ExoMars RLS Simulator. Carbon signatures acquired from the cratered material show an increase in molecular disorder (producing more reactive carbon) that likely result from intense shearing forces. This result has implications for potential (past) Martian habitability because impacted, reduced carbon may become more biologically accessible.